Process evaluation methods and results from the Health in Pregnancy and Postpartum (HIPP) randomized controlled trial - Sara Wilcox; Alicia A. Dahl; Alycia K. Boutté; Jihong Liu; Kelsey Day; Gabrielle Turner-McGrievy; Ellen Wingard (BMC Pregnancy and Childbirth, 2022)
Abstract Background Excessive gestational weight gain has increased over time and is resistant to intervention, especially in women living with overweight or obesity. This study described the process evaluation methods and findings from a behavioral lifestyle intervention for African American and white women living with overweight and obesity that spanned pregnancy (≤ 16 weeks gestation) through 6 months postpartum. Methods The Health in Pregnancy and Postpartum (HIPP) study tested a theory-based behavioral intervention (vs. standard care) to help women (N = 219; 44% African American, 29.1 ± 4.8 years) living with overweight or obesity meet weight gain guidelines in pregnancy and lose weight in postpartum. Participants completed process evaluation surveys at 32 weeks gestation (n = 183) and 6 months postpartum (n = 168) regarding their perceptions of most and least helpful aspects of the intervention. A database tracked delivery and receipt of intervention components (in-depth counseling session, telephone calls, podcasts). Descriptive statistics are used to report fidelity, dose, and participants’ perceptions. We also tested whether dose of behavioral intervention components was associated with gestational weight gain and 6-month postpartum weight retention with linear regression models controlling for baseline age and gestational weeks, receipt of Medicaid, race, parity, and marital status. A content analysis was used to code and analyze responses to open-ended survey questions. Results Over 90% of participants (both groups) would recommend the program to a friend. Implementation fidelity was moderately high and greater in pregnancy than postpartum for all intervention components. Dose received and participants’ ratings of the in-depth counseling session and telephone calls were more favorable than podcasts. The Facebook group was not perceived to be very helpful, likely because of low participant interaction. Although podcasts were created to reinforce call topics, this redundancy was viewed negatively by some. More calls completed and more podcasts downloaded related to lower gestational weight gain (p < .05). Conclusion Study findings underscore challenges in engaging this important but busy population, especially during the postpartum period. Trial registration: The study was registered at clinicaltrials.gov (NCT02260518) on 10/09/2014. https://clinicaltrials.gov/ct2/show/NCT02260518 .